Real-life Data for Tenofovir Alafenamide Fumarate Treatment of Hepatitis B: the Pythagoras Cohort - Karasahin, Omer; Kalkan, Irem Akdemir; Dal, Tuba; Toplu, Sibel Altunisik; Harputoglu, Murat; Mete, Ayse Ozlem; Celen, Mustafa K. (Brieflands, 2021)
Background: Chronic hepatitis B (CHB) is a viral infection that can result in life-threatening conditions, such as hepatocellular carcinoma and cirrhosis. Tenofovir, which is used for the treatment of CHB, is a nucleotide analog that inhibits HBV-DNApolymerase and has two formulations: disoproxil and alafenamide. In contrast to tenofovir disoproxil fumarate (TDF), tenofovir alafenamide fumarate (TAF) penetrates the whole hepatocyte without being eliminated due to its longer plasma half-life and greater plasma stability. As a result, side effects such as proximal renal tubulopathy and loss of bone density are less common in the treatment of TAF and have similar efficacy to TDF. Objectives: The purpose of the study was to evaluate the effectiveness and reliability of TAF using real-life data. Methods: This retrospective cohort study was carried out in secondary or tertiary healthcare centers in southern Turkey. A total of 480 patients aged 18 years and older were administered TAF for an appropriate indication by the infectious diseases and gastroenterology clinics of the healthcare centers participating in this study. The data collected at t = 0, t =3, and t = 6 months of treatment were analyzed. The chi-square, Mann-Whitney U, Friedman, Wilcoxon, Cochran's Q, and McNemar's tests were used. Results: The mean age of the patients was 47.40 +/- 14.5, and 327 of them (68.1%) were male. A total of 78.1% of the 480 patients who underwent the TAF treatment had previous antiviral therapy experience (TDF, n =340; 70.8 %), and 21.9% were treatment-naive. The most common reasons for the initiation of TAF treatment were the use of drugs affecting bone mineral density (BMD) (42.9%) and osteoporosis (22.3%). Patients who had taken TDF experienced a significant improvement in glomerular filtration rate (GFR), hip and spine T-scores, and phosphorus levels from t = 0 months tot = 6 months after switching to TAF (P < 0.05). For this group, no statistically significant difference was observed concerning LDL and cholesterol levels from t= 0 months to t = 6 months. Side effects were reported by 5.7% of patients in the third month and 7.1% in the sixth month, with the most common side effect being hair loss (1%). Conclusions: TAF was found to be an effective and safe alternative to TDF with lower incidences of its long-term effects, such as nephrotoxicity and decreased bone density.
Keywords: Bone Mineral Density; Hepatitis B; Chronic Hepatitis B; Glomerular Filtration Rate; Tenofovir Alafenamide; Real Life; Tenofovir Disoproxil